Pemetaan Daerah Rawan Erosi di Kecamatan Purwosari, Kabupaten Gunungkidul Berbasis Model USLE - Deyan Arum Sitaresmi; Virsha Shofiyani; Aisahrul Hutami; Ashila Fitria Zahra; Muhamad Imron Rosadi; Gita Sukma Irvi Lestari; Wandi Tri Januar (Geosfera: Jurnal Penelitian Geografi, 2025)
This study aims to map the erosion hazard levels in Purwosari District, Gunungkidul Regency, Special Region of Yogyakarta, by integrating the Universal Soil Loss Equation (USLE) model with Geographic Information Systems (GIS). The study is motivated by the geomorphological conditions of the karst area, which are inherently susceptible to erosion, coupled with predominant land use in the form of rainfed fields and paddies with minimal vegetation cover. The methodology employs a quantitative descriptive-analytical approach consisting of four main stages: land cover classification, calculation of USLE parameters (R, K, LS, C, and P), spatial overlay to generate the erosion hazard level map, and field validation through observations and interviews with local farmers. The results indicate that approximately 80% of Purwosari District falls within the very low to low erosion hazard categories, while 18.74% is classified as moderate, and the remaining, albeit very small portion, is categorized as high to very high, predominantly in areas with steep slopes and limited vegetation. These findings underscore the need for implementing soil conservation strategies tailored to local characteristics to mitigate the rate of erosion, particularly in highly vulnerable areas. This research is expected to serve as a reference for formulating sustainable land resource management policies in karst regions.